PENGARUH KUALITAS DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH WORD OF MOUTH (STUDI KASUS RUMAH TENUN PUTA DINO TIDORE) - Fabanyo, Rohani; Haji, Sulfi Abdul; Hi. Yusuf, Ibnu Sina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
ABSTRACTObjective: This study aims to determine the influence of product quality and price on purchasing decisions mediated by word of mouth in the case of the Puta Dino Tidore weaving house.Methodology: The population in this study were all visitors to the Puta Dino Tidore weaving house. The number of samples in this research is the number of indicators/items x 7, namely 15 x 7 = 105 respondentsFinding: The partial hypothesis and simultaneous hypothesis are accepted, because the alpha value is smaller than 5%, except for the first hypothesis there is no significant effect.Conclusion: The results of this research indicate that product quality does not have a significant effect on purchasing decisions; price has a significant effect on purchasing decisions; product quality has a significant effect on word of mouth promotion; price has a significant effect on word of mouth promotion; Word of Mouth has a significant influence on purchasing decisions. Product quality has a significant influence on purchasing decisions through word of mouth mediation. Price has a significant influence on purchasing decisions through word of mouth.Â